2000
DOI: 10.1063/1.372033
|View full text |Cite
|
Sign up to set email alerts
|

Electrical characteristics of thin Ta2O5 films deposited by reactive pulsed direct-current magnetron sputtering

Abstract: Articles you may be interested inModel relating process variables to film electrical properties for reactively sputtered tantalum oxide thin films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…From a practical point of view, the material possesses good dielectric properties at high frequencies (100 kHz). The dielectric constant (18.5) and the dissipation factor (4 Â 10 À 3 ) are comparable to more popular oxides such as Ta 2 O 5 [13]. The temperature coefficient of capacitance (TCC) is about 240 ppm/-C in the À 50 -C to + 150 -C range (extracted from Fig.…”
Section: Resultsmentioning
confidence: 95%
“…From a practical point of view, the material possesses good dielectric properties at high frequencies (100 kHz). The dielectric constant (18.5) and the dissipation factor (4 Â 10 À 3 ) are comparable to more popular oxides such as Ta 2 O 5 [13]. The temperature coefficient of capacitance (TCC) is about 240 ppm/-C in the À 50 -C to + 150 -C range (extracted from Fig.…”
Section: Resultsmentioning
confidence: 95%
“…1 Tantalum pentoxide (Ta 2 O 5 , an electrical insulator with dielectric constant > 26, is one of the best candidates to be used as a gate barrier instead of SiO 2 in field effect transistors and in DRAM capacitors. 2 3 Several techniques such as electron beam gun evaporation, 4 and reactive pulsed direct-current magnetron sputtering 5 have been used to fabricate highly insulating tantalum pentoxide capacitor films. Tip-induced Scanning Probe Lithography (SPL) technique has been used to create nanostructures below 100 nm 6 on semiconductors [7][8][9] and metals surfaces such as chromium, 10 titanium, 11-12 niobium 13 and on tantalum films in contact mode.…”
Section: Introductionmentioning
confidence: 99%
“…18 Pulsed reactive dc magnetron sputtering has been developed to improve the quality of oxide films by avoiding arcing. [18][19][20][21] For a pulsed reactive dc magnetron sputtering, the polarity of the power supplied to the target oscillates between negative and positive potential. During the positive period, the insulating layer on the target surface is discharged and arcing is prevented.…”
Section: Introductionmentioning
confidence: 99%
“…From the defect density found in the dielectric oxide film and the deposition rate, it is estimated that the typical operating frequencies for pulsed dc magnetron sputtering of oxides should be in the 10-250 kHz range. [18][19][20][21] Belkind et al 18 suggested that arcing could be avoided when pulsing frequency is higher than a critical frequency that depends on the cathode current and reverse time. So far, very few attempts have been made to study the pulsing effect on the electrical properties of oxide films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation